A Reflective Photoplethysmogram Array and Channel Selection Algorithm for Weighing Scale Based Blood Pressure Measurement - Carek, Andrew M.; Jung, Hewon; Inan, Omer T. (IEEE sensors journal, 2020)
The most common form of blood pressure (BP) monitoring outside of clinical settings is an oscillometric cuff; however, such cuffs tend to be cumbersome and inconvenient. Less obtrusive systems requiring minimal effort from the user would allow for cardiovascular monitoring seamlessly in daily life and relieve much of the burden of regular blood pressure monitoring. In this work, we leverage the concept of pulse transit time (PTT) to track BP using a weighing scale-based system on which a subject simply stands quietly to obtain a measurement. To extract the proximal and distal timing references for PTT, a force plate measured the initial mechanical motion of the body in response to cardiac ejection while an optical sensor array mounted directly on the force place measured the pulse wave arrival at the sole. To evaluate the method, we recruited 16 young and healthy subjects. Seated and standing measurements first verified the effectiveness of the sensor array to extract a reliable distal timing reference. Then, subjects underwent various physiological perturbations to establish a correlation curve between measured BP and a best-case estimation of BP using PTT. By using the BCG and array of PPG sensors, PTT-estimated BP tracked changes well in diastolic ( r = 0.80 ± 0.12) and systolic ( r = 0.77 ± 0.23) pressures. This best-case estimation resulted in an error of 2.6 ± 1.2 mmHg for diastolic and 5.6 ± 2.7 mmHg for systolic pressures. Our work allows the user to passively monitor BP during common weighing scale measurement, potentially improving the ease of longitudinal at-home care.